New halogenated C15 acetogenins from Okinawan sea hare Aplysia dactylomela. (13th August 2022) - Matsuyama, Koushi; Inoue, Tomoe; Muroga, Tomoki; Arima, Naomichi; Doe, Matsumi; Tani, Fumito; Ookawa, Yuka; Okamoto, Yuuka; Onitsuka, Satoaki; Okamura, Hiroaki; Iwagawa, Tetsuo; Hamada, Toshiyuki
Abstract: Two new C15 acetogenins 1 and 2, along with four known sesquiterpenes isolaurenisol (3 ), laurokamurene D (4 ), itomanol (5 ), and acetylelatol (6 ), were isolated from sea hare Aplysia dactylomela . The structures, including the relative stereochemistries, of 1 and 2 were determined based on spectroscopic evidence. Finally, the in vitro cytotoxicities of the six compounds against S1T cells, an adult T-cell leukemia cell line, were evaluated. Graphical abstract: Image 1